Public Administration’s Adaptation to COVID-19 Pandemic – Czech, Hungarian, Polish and Slovak Experience - Matej Horvat; Wojciech Piątek; Lukáš Potěšil; Krisztina F. Rozsnyai (Central European Public Administration Review)
The pandemic of the infectious disease Covid-19 affected everyday life including public administration. In order to proceed with its duties, public administration had to adapt to these new and unprecedented conditions. The main goal of the article is to assess how public administration bodies adapted to the Covid-19 pandemic, especially in terms of the principle of the speed of procedure in the sense of the right to a fair trial within a reasonable time. In order to achieve this goal, the article focuses on public administration’s adaptation to the pandemic from the perspective of the Visegrad Group countries (V4). It analyses the digitalisation of public administration in relation to delivery, speed of procedure, usage of new technologies, as well as several other areas of public life affected by the pandemic. Specific examples from all V4 countries are analysed and compared in order to identify which approaches were taken by public administration, how they changed the way public administration carried out administrative procedures, and which values were decisive for these changes. Based on these examples, the article concludes that the approach taken by respective legislatures and public administrations in the V4 region complies with the law, but also presents several exceptions.